Healthcare workers’ mental health in pandemic times: the predict role of psychosocial risks - Barros, Carla (2022)
Healthcare workers perform an emotionally exhausting daily work activity, making them prone to occupational hazards, namely psychosocial ones. This study aims to assess the impact of psy chosocial risk factors on healthcare workers’ mental health. A cross-sectional study was developed between May and June of 2021 with 479 healthcare workers from Portuguese hospitals. The Depression, Anxiety and Stress Scale was used to assess mental health, and psychosocial risks were assessed through the Health and Work Survey e INSAT. Statistical analysis was performed to identify the psychosocial risk factors related to anxiety, depression, and stress. Subsequently, a multiple linear regression was performed to identify the models that better explained psychosocial risk factors’ relationship with anxiety, depression, and stress. Data showed a strong exposure to psychosocial risks. Work pace and intensity, work relation ships, and emotional demands stood out with higher global average percentages for yes answers to “exposure and discomfort.” The analysis of the b values and p-values from the multiple linear regression shows that some cross-sectional psychosocial risks are predictors of anxiety and stress dimensions, and other psychosocial risks differ in the two mental health dimensions. However, it is important to highlight that healthcare workers still showed great joy and pleasure in performing their work activities. Support network development in the work environment is needed to prevent healthcare workers’ emotional stress and promote their psychological well-being. Therefore, new research is essential to understand the psychosocial risks that affect healthcare workers and assess the less visible effects of workehealth relationships